A comparison study of 'motivation–intention–behavior' model on household solid waste sorting in China and Singapore. (20th February 2019) - Fan, Bo; Yang, Wenting; Shen, Xingchen
Abstract: Economic growth and rapid urbanization have resulted in various urban problems related to sustainable development. The continuous increase in household solid waste has become a significant concern worldwide, while waste sorting has been regarded as an effective method for waste reduction. However, the low recycling rates of household solid waste are common in many countries. Accordingly, our study used theory of planned behavior (TPB) to construct a "motivation–intention–behavior" theoretical model for the systemic illustration of the antecedents of household solid waste sorting behavior. A comparative study was performed to explore the similarities and differences between the determinants of sorting behavior in Shanghai and Singapore. A survey of 1100 urban residents from these two places was conducted to validate our model by using structural equation modeling. Findings indicated that general and specific environmental motivations substantially influenced behavioral intention. Moreover, the direct influence and moderating effect of contextual factors on waste sorting behavior are significant. Habitual factors also have a significant effect on behavior. Our study enhanced the understanding of the determinants of household solid waste sorting behavior and improved TPB by simultaneously adding motivation, contextual, and habitual factors. Moreover, our study used theory of environmental interventions as basis to provide several suggestions that will improve existing policies. These suggestions can be valuable references for waste management in megacities. Highlights: A comparative study of the impact of household solid waste sorting behavior between Shanghai and Singapore was conducted. A theoretical model including motivational, contextual and habitual factors was proposed based on theory of planned behavior. Results showed that general and specific environmental motivation factors significantly influence sorting behavior. We found that the direct and moderating effect of contextual factors and the influence of habitual factors are significant. Several suggestions for the existing policies were proposed based on theory of environmental interventions.